A Rising Shudders: America’s Against the Growing Challenge of China (Global Journal of Human-Social Science, 2022)
The critical scope of competition between China and the U S Takes us bygone to the Cold War era While the communist party of China has done to launch a new era between a great-power competition named Chinese a technology developing a world-class military and political influence has grown around the globe and the country has emerged as a pioneer in much- advanced technology areas including artificial intelligence economics autonomy quantum computing etc to achieve its interests
Keywords: US; CHINA; hegemony; escalation; challenges five eyes intelligence